Refining prediction of survival after TIPS with the novel Freiburg index of post-TIPS survival - Bettinger, Dominik; Sturm, Lukas; Pfaff, Lena; Hahn, Felix; Kloeckner, Roman; Volkwein, Lara; Praktiknjo, Michael; Lv, Yong; Han, Guohong; Huber, Jan Patrick; Boettler, Tobias; Reincke, Marlene; et al. (Journal of hepatology, 2021)
Background & Aims - Transjugular intrahepatic portosystemic shunt (TIPS) implantation is an effective and safe treatment for complications of portal hypertension. Survival prediction is important in these patients as they constitute a high-risk population. Therefore, the aim of our study was to develop an alternative prognostic model for accurate survival prediction after planned TIPS implantation. - Methods - A total of 1,871 patients with de novo TIPS implantation for ascites or secondary prophylaxis of variceal bleeding were recruited retrospectively. The study cohort was divided into a training set (80% of study patients; n = 1,496) and a validation set (20% of study patients; n = 375). Further, patients with early (preemptive) TIPS implantation due to variceal bleeding were included as another validation cohort (n = 290). Medical data and overall survival (OS) were assessed. A Cox regression model was used to create an alternative prediction model, which includes significant prognostic factors. - Results - Age, bilirubin, albumin and creatinine were the most important prognostic factors. These parameters were included in a new score named the Freiburg index of post-TIPS survival (FIPS). The FIPS score was able to identify high-risk patients with a significantly reduced median survival of 5.0 (3.1-6.9) months after TIPS implantation in the training set. These results were confirmed in the validation set (median survival of 3.1 [0.9-5.3] months). The FIPS score showed better prognostic discrimination compared to the Child-Pugh, MELD, MELD-Na score and the bilirubin-platelet model. However, the FIPS score showed insufficient prognostic discrimination in patients with early TIPS implantation. - Conclusions - The FIPS score is superior to established scoring systems for the identification of high-risk patients with a worse prognosis following elective TIPS implantation. - Lay summary - Implantation of a transjugular intrahepatic portosystemic shunt (TIPS) is a safe and effective treatment for patients with cirrhosis and clinically significant portal hypertension. However, risk stratification is a major challenge in these patients as currently available scoring systems have major drawbacks. Age, bilirubin, albumin and creatinine were included in a new risk score which was named the Freiburg index of post-TIPS survival (FIPS). The FIPS score can identify patients at high risk and may guide clinical decision making.
Gesehen am 21.02.2022